2022
DOI: 10.3390/ijms23179534
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of AMPKα1 in Regulating Autophagy and Mitochondrial Respiration in IL-15-Stimulated mTORC1Weak Signal-Induced T Cell Memory: An Interplay between Yin (AMPKα1) and Yang (mTORC1) Energy Sensors in T Cell Differentiation

Abstract: Two common γ-chain family cytokines IL-2 and IL-15 stimulate the same mammalian target of rapamycin complex-1 (mTORC1) signaling yet induce effector T (TE) and memory T (TM) cell differentiation via a poorly understood mechanism(s). Here, we prepared in vitro IL-2-stimulated TE (IL-2/TE) and IL-15-stimulated TM (IL-15/TM) cells for characterization by flow cytometry, Western blotting, confocal microscopy and Seahorse-assay analyses. We demonstrate that IL-2 and IL-15 stimulate strong and weak mTORC1 signals, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…And the enhanced HIF-1α-dependent growth of tumors is associated with increased multifunctionality of CD8 + TILs [112]. In addition, HIF-1α upregulation contributes to the metabolic switch from FAO to glycolysis, thereby promoting effector T cell differentiation [113,114]. For CD4 + T cells, HIF-1α-mediated glycolysis activity and metabolic reprogramming are important for their differentiation and function [115][116][117][118].…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…And the enhanced HIF-1α-dependent growth of tumors is associated with increased multifunctionality of CD8 + TILs [112]. In addition, HIF-1α upregulation contributes to the metabolic switch from FAO to glycolysis, thereby promoting effector T cell differentiation [113,114]. For CD4 + T cells, HIF-1α-mediated glycolysis activity and metabolic reprogramming are important for their differentiation and function [115][116][117][118].…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…High levels of IL-15 contribute to the improvement of insulin resistance in postmenopausal women with metabolic syndrome [ 226 ]. IL-15 triggers autophagy in the immune cells, mediating homeostasis and the survival of these cells [ 227 , 228 ]. IL-6 is a pleiotropic cytokine with respect to insulin resistance; while numerous studies have indicated its association with insulin resistance [ 226 229 ], others have reported its insulin-sensitizing effects [ 230 , 231 ].…”
Section: Skeletal Muscle Tissuementioning
confidence: 99%
“…For example, Ara et al . described the effects of the pro-survival cytokine IL-15 on T cells, activating AMPKα1 and upregulating ULK1, ATG7, the mitochondrial fusion protein optic atrophy-1 (OPA1), TFAM, AQP9, CPT1α and Complex I mitochondrial biogenesis protein levels respectively, while also leading to reliance on FAO with concomitant downregulation of hypoxia-inducible factor (HIF)-1α and thus glycolysis [ 73 ]. Interestingly, this mechanism involving γ-chain family cytokines was also shown to be crucial for the complete induction of autophagy in response to TCR and CD28 engagement.…”
Section: Relationship Between Cytokine Release and Autophagy In T Cellsmentioning
confidence: 99%